Glycoprotein Ib Can Mediate Endothelial Cell Attachment to a von Willebrand Factor Substratum - Beacham, Dorothy A; Cruz, Miguel A; Handin, Robert I (Thrombosis and Haemostasis, 1995)
Introduction of single amino acid substitutions into the C-terminal Arg-Gly-Asp-Ser (RGDS) site of von Willebrand Factor, referred to as RGD mutant vWF, selectively abrogated vWF binding to platelet glycoprotein IIb/IIIa (GpIIb/IIIa, αIIbβ3 and abolished human umbilical vein endothelial cell (HUVEC) spreading, but not attachment, to RGD mutant vWF (Beacham, D. A., Wise, R. J., Turci, S. M. and Handin, R. I. 1992. J. Biol. Chem. 167, 3409-3415). These results suggested that in addition to the vitronectin receptor (VNR, αvβ3), a second endothelial membrane glycoprotein can mediate HUVEC adhesion to vWF. HUVEC attachment to wild-type (WT) and RGD-mutant vWF was reduced by two proteins known to block the vWF-platelet glycoprotein Ib/IX (GpIb/IX) interaction, the monoclonal antibody AS-7 and the recombinant polypeptide, vWF-A1. The addition of cytochalasin B or DNase I to disrupt potential GPIbα-cytoskeletal interactions enhanced the immunoprecipitation of endothelial GPIbα, caused HUVEC to round up, and increased HUVEC adhesion to RGD mutant vWF. These results indicate that while the VNR is the primary adhesion receptor for vWF, endothelial GPIbα can mediate HUVEC attachment to vWF. GpIb-dependent attachment could contribute to HUVEC adhesion under conditions when cell surface expression of the VNR is downregulated, and VNR-dependent adhesion is reduced.